Digitisation of Library Material in Europe: Problems, Obstacles and Perspectives anno 2007 - Nielsen, Erland Kolding (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
This paper is a short introductory policy paper about the state-of-the-art of digitisation of library material in Europe, seen from the chief executive point of view of a big national and university library in the autumn of 2007. It focuses on current problems, obstacles, and some perspectives. What has been achieved, what are the problems and obstacles in terms of especially mass digitisation in the light of the so-called Google challenge and the response by the Commission of the European Union, and what are the consequences likely to be?